Political freedom and human rights 20 years after the fall of the Berlin Wall - Belardinelli, Sergio; Langan, Jeff; Lobkowicz, Nikolaus (Acta Philosophica, 2009)
Sergio Belardinelli, Il Sessantotto e l’Ottantanove: gli esiti di due rivoluzioni Jeff Langan, Plato’s Lesson: The Chances after a Revolution Nikolaus Lobkowicz, Marxism died before 1989 but many thinkers of the free world ignore it